Prolonged Detection of Japanese Encephalitis Virus in Urine and Whole Blood in a Returned Short-term Traveler. (27th September 2017) - Huang, G Khai Lin; Tio, Shio Yen; Caly, Leon; Nicholson, Suellen; Thevarajan, Irani; Papadakis, Georgina; Catton, Mike; Tong, Steven Y C; Druce, Julian
Abstract: We describe a fatal case of Japanese encephalitis virus infection following short-term travel to Thailand. Viral RNA was detected in urine and whole blood out to 26 and 28 days, respectively, after the onset of symptoms. Live virus was isolated from a urine specimen from day 14.